Assentamento recanto da esperança: memórias que compõem a sua história - Neri, Tatiana Cybelle Rocha (Universidade Federal Rural do Semi-Árido, 2020)
Talking about the history of a settlement leads us to understand what the agrarian reform project is like, how rural social movements are organized and the relationship that rural peoples have in relation to the struggle and conflict for access to land. The objective of the research that generated the elaboration of this work was to know the history of struggle and conflict of lands of Fazenda São João, through the memories and narratives of the protagonists inserted in this process of struggle that resulted in the Recanto da Esperança-RN Settlement Project. To achieve this goal, five subjects were interviewed (05), two men and (03) three women, former employees of Fazenda São João, community leader and women of the community, who worked during the period of this conflict, as well as representatives of community interests at that time. The research developed is of a qualitative nature and counted as a theoretical reference, among other authors, For MINAYO (2001, p.22), “qualitative research answers very particular questions. It is concerned, in the social sciences, with a level of reality that cannot be quantified. The interviewees' narratives bring moments of struggle, tears, fear, anguish, joy, violence and death threats, in a rescue of their memories, bringing to the fore the experiences they had until achieving the victory of the settlement institution guaranteeing their place of belonging and to a better quality of life, with better prospects, both economically and socially for the residents of the Settlement.
Keywords: Memorias; Reforma agraria; Povos do Campo; Assentamento; Memoirs; Land reform; Countryside people; Settlement; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL